Risk Factors of Repeat Diarrhea In The Mining Region Community In Morosi District - Titi Saparina L; Solihin; Mona Marsita (Miracle Journal of Public Health, 2023)
Morosi sub-district is one of the sub-districts located in mining areas that have low access to latrine sanitation and clean water sources where many people are still affected by recurrent diarrhea. with data in 2019 totaling 216 cases, in 2020 totaling 278 cases and in 2021 totaling 310 cases. The purpose of this study was to determine the risk factors for recurrent diarrhea in the community in the mining area of ​​Morosi District. This type of research uses a case-control study with a retrospective approach. The population in this study amounted to 310 people. The sampling technique used is a simple random sampling technique. The sample in this study amounted to 152 samples of which 76 cases and 76 controls. The analysis method uses the Chi-Square Test and the Odds Ratio Test. The results of the Odds Ratio test for latrine ownership obtained an OR value of 3.735. The results of the Odds Ratio test for nutritional status obtained an OR value of 0.903. The results of the Odds Ratio test for clean water sources obtained an OR value of 3.483. The community is also expected to be able and willing to improve the prevention and control of risk factors for recurrent diarrhea in a comprehensive and sustainable manner.